A ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI BILANGAN BULAT KELAS VII SMP N 1 SENAYANG: ANALISIS - Muhammad Marqozi; Indah Widiati; Dedek Andrian; Faridatul Masruroh (Journal of Research in Science and Mathematics Education (J-RSME), 2023)
Purpose: The objective of this study is to analyze the errors committed by students while solving problems related to integers. Methodology: The research methodology employed is descriptive qualitative research. The participants of the study consisted of 22 seventh-grade students from SMPN 1 Senayang, Riau Islands, Indonesia. Data collection for this study involved the utilization of both testing and non-testing techniques. The testing technique employed descriptive instrument tests, while the non-testing techniques included observation guidelines, interview guidelines, and documentation. Data analysis for this study encompassed several stages, including data collection, data reduction, data presentation, and drawing conclusions. Findings: The research findings revealed the following: (1) Student code 12 made errors in utilizing formulas, solving operations, and drawing conclusions. (2) Student code 6 made errors in completion operations and concluding their answers. (3) Student code 2 made errors in employing formulas, solving operations, and concluding answers. (4) Student code 16 made errors in utilizing formulas, solving operations, and drawing conclusions. (5) Student code 19 exhibited errors in comprehension, formula usage, solving operations, and drawing conclusions. Significance: (6) Student code 22 made errors in utilizing formulas, solving operations, and concluding answers.